Strategi Pengembangan Organisasi Kemahasiswaan di Perguruan Tinggi Islam Baru: Studi Kasus BEM STAI Alif Laam Miim Surabaya - Moh. Yusuf Bahtiar (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This study aims to analyze the development strategy of student organizations in a newly established Islamic university through a case study of the Student Executive Board (BEM) of STAI Alif Laam Miim Surabaya. New Islamic universities often face various challenges in managing student organizations, such as limited human resources, minimal experience of student organizations, and weak institutional development systems. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation of BEM activities. The results of the study indicate that organizational development is carried out through three main strategies, namely: (1) strengthening spirituality and prophetic leadership values, (2) developing cadres through training and socio-religious activities, and (3) synergy between supervisors and students in building a productive and religious organizational culture. The results of this study provide implications for the development of student institutions in other Islamic universities so that they are able to build organizations that are adaptive, professional, and have an Islamic character.